Activation of the STAT1 Pathway Accelerates Periodontitis in Nos3-/- Mice. (August 2019) - Wei, W.; Xiao, X.; Li, J.; Ding, H.; Pan, W.; Deng, S.; Yin, W.; Xue, L.; Lu, Q.; Yue, Y.; Tian, Y.; Wang, M.; et al.
Early studies on the etiology and pathogenesis of hypertension have shown that it has a considerable association with inflammation and the immune response as well as periodontitis. Clinical studies have also shown that hypertension can promote the periodontal tissue destruction caused by periodontitis. However, the underlying mechanisms remain unclear. This study aimed to explore the possible mechanisms of how hypertension aggravates periodontitis. Treatment with or without the signal transducer and activator of transcription 1 (STAT1) inhibitor fludarabine was performed in an endothelial nitric oxide synthase gene knockout-related ( Nos3 -/- ) mouse model with the hypertension phenotype of periodontitis induced by bacteria. Micro–computed tomography, immunohistochemistry, Western blot, quantitative reverse transcription polymerase chain reaction, immunofluorescence, and ELISA were performed. We demonstrated that Nos3 -/- -related hypertension increases bone resorption and periodontal destruction in periodontitis lesion areas, which can be inhibited by the STAT1 inhibitor. Experimental data also showed that Nos3 -/- significantly increased macrophage infiltration and proinflammatory cytokine expression in the periodontitis lesion area, which is dependent on the angiotensin II–induced STAT1 pathway. Inhibition of STAT1 in vivo can decrease the expression of proinflammatory cytokines and macrophage infiltration. Furthermore, data in this study showed that Nos3 -/- -related hypertension further downregulated the STAT3 anti-inflammatory function and its downstream chemokine expression in a STAT1-dependent manner. By applying RAW 264.7 and L929 cell lines and monocytes isolated from Nos3 -/- mice, we confirmed that activation of the STAT1 pathway inhibits STAT3 and its downstream pathway and promotes inflammatory cytokine expression in vitro. Collectively, our current study demonstrated that STAT1 plays an indispensable role in the Nos3 -/- -related hypertension with aggravation of periodontitis, suggesting that STAT1 may be a key target for the treatment of periodontitis with hypertension.